The future of surplus food redistribution in the UK: Reimagining a 'win-win' scenario. (April 2022) - Papargyropoulou, Effie; Fearnyough, Kate; Spring, Charlotte; Antal, Lucy
Highlights: Policy agenda for the future of Surplus Food Redistribution in the UK. SFR paradoxically reinforces the same problems it attempts to solve. Reject the SFR 'win-win' narrative; tackle systematic food overproduction and poverty. Deliver food security within planetary boundaries. Balance uneven power distribution amongst food systems actors. Abstract: Surplus food redistribution (SFR) is hailed as a 'win-win' strategy to address both household food insecurity and food waste. However, SFR is condemned as being a 'band-aid' solution that addresses neither the fundamental socio-economic causes of poverty, nor the systematic roots of food waste. This research aims to set an agenda for the future of SFR in the UK for the next five to 10 years, including policy interventions required to achieve this future. To this end, it critically examines the motivations, challenges and perspectives on SFR in the UK, explores the ideal future scenario of SFR (by reimagining the 'win-win' scenario), and identifies intervention pathways leading to this future. It achieves this through a participatory, mixed methods research design of 17 interviews, explorative scenario building and normative back casting exercises with 40 relevant SFR stakeholders across the private, public and third sectors. It concludes that SFR paradoxically reinforces the same problems it attempts to solve. The future of SFR lies in truly sustainable food systems that meet the needs of the people and deliver socio-economic benefits whilst respecting planetary boundaries. In this future, SFR is no longer required as a solution for food waste or household food insecurity. Finally, the study identifies five pathways leading to this future: i) rejecting the SFR 'win-win' narrative ii) tackling systematic food overproduction iii) eradicating poverty iv) balancing uneven power distribution amongst food systems actors, and v) delivering food security within planetary boundaries. The proposed interventions are relevant to food and waste policies, and offer insights to transition pathways for sustainable food and other socio-technical systems.